Penerapan Metode Electre Untuk Penilaian Kinerja Kepegawaian Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Pemalang - Rusito; Bayu Agus Pamabudi; Sumaryanto; Febryantahanuji (LPPM Universitas Sains dan Teknologi Komputer, 2022)
Assessment of employee performance is expected to know precisely the success in completing work. Employee performance appraisal is also useful for companies in providing feedback to employees and can be used as a basis for agencies to evaluate employee performance. Most government services currently utilize information technology as an information service to the public and the agency's internal services. In institutions, it is necessary to increase and develop the capabilities, knowledge and skills of its human resources, so that it is expected to be able to produce apparatuses that have competitive competencies. Therefore, the authors designed and built an employee performance appraisal system which was implemented using Electre and Web-based and Android methods. It is expected to be able to assist agencies in evaluating employee performance so that they can remain consistent in carrying out their duties as Civil Servants (PNS) within the scope of services to the community. This research uses the R&D method. researchers only use up to step 6. Based on the results of trials of 10 respondents who have assessed the decision making system using the electre method, that the application of employee performance appraisal using aggregate ranking can help provide information on the level of employee performance based on predetermined criteria. Respondents agree that this system is more efficient in assessing employee performance with an average of the old system = 43.50% while the new system is = 84.50%.